A new bidirectional intraperitoneal and systemic induction chemotherapy (BISIC) for the peritoneal metastasis from gastric cancer in neoadjuvant setting. Issue 2 (2014) - Y, Yonemura; E, Canbay; Y, Endou; H, Ishibashi
No abstract available